PENGEMBANGAN KURIKULUM PENDIDIKAN PARIWISATA BERKELANJUTAN: USAHA PERJALANAN DAN DESTINASI WISATA, HOSPITALITY, KULINER - Mochammad Taufik Ramadhan Zain; Elly Malihah (Kepariwisataan: Jurnal Ilmiah, 2022)
The tourism industry sector is one of the industries that is developing at this time. Tourism studies are very broad and can affect other sciences, one of which is education. The existence of an appropriate education curriculum related to tourism is very important in developing tourism knowledge and skills so as to realize sustainable tourism education. This study uses library research using descriptive analysis method by collecting literature study data by studying book references, articles, and browsing the internet, as well as literature reviews related to the sustainable tourism education curriculum. The purpose of writing is to provide tourism information as an independent science and to describe the development of a sustainable tourism education curriculum that includes travel business, hospitality and culinary accommodation.Keywords: Tourism Industry; Tourism Science; Tourism Education Curriculum; Sustainable Tourism Education